On the sums of a random number of random variables - Szász, D.; Freyer, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Саас, Б. Фрайер. Одна задача теории суммирования со случайным индексом D. Sasas, B. Frajeris. Vienas sumavimo su atsitiktiniu indeksu teorijos uždavinys